A new active compound from Centaurea species - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2006)
The extract containing sesquiterpene lactones of Centaurea iberica (Asteraceae) isolated was separated and a steroidal compound, which is stigmast-1,5-dien-3 beta-ol, was purified. The chemical structure was established based on spectroscopic data (UV, IR, MS, H-1 NMR, C-13 NMR). Both the extract and the compound showed significant antioxidant and antimicrobial activities.
Keywords: Centaurea; antimicrobial; stigmast-1,5-dien-3 beta-ol